THE FLORA OF “HERGHELIE MARSH” NATURAL RESERVE (CONSTANŢA COUNTY) - MARIUS FAGARAS (Journal of Plant Development, 2007)
The paper’s aim is to present the floristic inventory and the main vegetation types of Herghelie Marsh, a less-known Natural Reserve placed near Mangalia city, in the proximity of the Black Sea shore area. Some considerations about the life forms, phytogeographical elements, ecological categories and rare or threatened taxa within this eutrophic marsh are also presented.